Bronkopneumonia dengan Suspek Tuberkulosis Paru, Trombositopenia ec Dengue Fever, Gizi Kurang, dan Imunisasi Tidak Lengkap pada Bayi Usia 9 Bulan: Sebuah Laporan Kasus - Herlingga Nirwana HR; Anselmus Libreya Sinulingga; Lariza Serafina Tobroni; Shinta Nareswari (CV. Jasa Sukses Abadi, 2026)
Bronchopneumonia remains the leading cause of morbidity in infants, especially in developing countries, and can be exacerbated by various comorbid factors such as poor nutritional status, incomplete immunization, and possible chronic infections. This case report aims to describe the clinical course, diagnostic challenges, and management of complex bronchopneumonia in a 9-month-old infant with suspected pulmonary tuberculosis and thrombocytopenia. The method used was a descriptive case report of a 9-month-old male infant who was treated with the main complaints of shortness of breath, chronic cough with phlegm, intermittent fever, and accompanied by weight loss. Data were obtained through anamnesis, physical examination, laboratory and radiological support examinations, and observation during treatment. The results showed that the patient had recurrent bronchopneumonia with findings of respiratory distress, early thrombocytopenia, an increase in LED levels indicating the onset of an inflammatory process, poor nutritional status, and incomplete basic immunization. A pediatric tuberculosis score of 3 led to suspicion of pulmonary TB, although definitive tests had not yet been obtained. Empirical antibiotic therapy, supportive therapy, nebulization, and chest physiotherapy provided gradual clinical improvement. In conclusion, bronchopneumonia in infants with multiple risk factors requires a holistic approach and high alertness to the possibility of chronic infection and comorbidities. A comprehensive evaluation of nutritional status, immunization, and environmental factors is essential to prevent recurrence and improve patient clinical outcomes.